2020
DOI: 10.1080/10872981.2020.1742964
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ motivation and academic performance: the mediating roles of self-efficacy and learning engagement

Abstract: Background: Motivation matters in medical students' academic performance. However, few studies have specifically examined how motivation and external environmental factors (e.g., institutions) affect medical students' performance with large-scale data sets. The roles of selfefficacy and learning engagement in the mechanisms that govern how motivation affects academic performance are still unclear. Objective: This study aims to advance a comprehensive understanding about the relationships between medical studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
182
0
14

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(216 citation statements)
references
References 27 publications
20
182
0
14
Order By: Relevance
“…Secondly, we observed a significant association between the level of self-efficacy and academic performance. Our findings are in agreement with previous studies [8,26,45,46] that suggest that the higher the level of self-efficacy, the better the academic performance. According to Schunk [47], those students who have a higher level of self-efficacy also tend to be more motivated, have higher aspirations, and to be more prepared to work hard to fulfil them [38].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Secondly, we observed a significant association between the level of self-efficacy and academic performance. Our findings are in agreement with previous studies [8,26,45,46] that suggest that the higher the level of self-efficacy, the better the academic performance. According to Schunk [47], those students who have a higher level of self-efficacy also tend to be more motivated, have higher aspirations, and to be more prepared to work hard to fulfil them [38].…”
Section: Discussionsupporting
confidence: 93%
“…Social skills are defined as the specific social abilities that are necessary to interact with, and relate to, others in an efficient, respectful, and mutually satisfactory manner [4]. Cognitive skills are the foundation for the construction and organization of knowledge and reasoning [5] and include abilities such as self-efficacy, defined as the belief in one's ability to face diverse situations [6][7][8]. Affective skills influence subjective wellness; subjective wellness could be colloquially described as happiness and comprises two components, namely cognitive and emotional.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with social cognitive theory ( Bandura, 1997 ) and self-efficacy theory ( Jiang et al, 2019 ; Codella et al, 2020 ; Li et al, 2020 ), we confirmed a mediating role of self-efficacy in the association between family support and student e-learning engagement, which means that promoting family support as a way to improve students’ sense of self-efficacy could help students put more energy into e-learning. As an important variable, self-efficacy can influence motivation and learning in student activities and play a decisive role in learner behavior by affecting various personal dimensions, such as focus, dedication, vigor, aspirations, and expectations ( Codella et al, 2020 ; Wu et al, 2020 ). Therefore, the higher the learning self-efficacy of students, the more they will be involved in learning.…”
Section: Discussionmentioning
confidence: 99%
“…It was deemed likely that the performance of students who withdrew from the podiatry program was strongly influenced by variables such as motivation and subject interest. For this reason, these students were excluded from the study (Molnar et al, 2012;Wu et al, 2020). It would be worthwhile investigating the multifactorial nature of student retention to evaluate whether lower scoring ATAR students are more likely to fail subjects or withdraw from the course so support strategies could be targeted towards these students.…”
Section: Limitationsmentioning
confidence: 99%